Prognosis of erosions development at gastric metaplasia of esophageal mucosa in patients with gastroesophageal reflux disease - Ye. K. Mastykova; M. R. Konorev; M. E. Matveyenko (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To determine prognostic value of diagnostics of gastric metaplasia of esophageal mucosa in development of erosions in patients with gastroesophageal reflux disease (GERD).Material and methods. Overall 100 patients with GERD have been enrolled in prospective comparative study: men – 57 (57%), women – 43 (43%), mean age was 50,2±18,1 years. Duration of follow-up was 3 to 10 years. Patients underwent esophagogastroduodenoscopy with guided biopsy of mucosa of the lower third of esophagus. Analysis of erosions frequency was carried out by 2 by 2 table (for χ2 criterion analysis).Results. The high diagnostic value of presence of gastric metaplasia of esophageal mucosa for prognosis of erosions in patients with GERD was revealed: sensitivity – was 80,7% (95% CI: 69,8–91,6%); specificity – 83,3% (95% CI: 72,6–94,0%); rate of correct prognoses – 82% (95% CI: 74,4–89,6%); relative risk of prognosticated outcome – 4,2; relative risk of different outcome – 0,2 (95% CI: 0,1–0,39%); odds ratio – 4,5 (95% CI: 1,6–12,7%).Conclusions. For the first time significant value of gastric metaplasia diagnostics in patients with GERD (p<0,001) for the prognosis of erosions of mucosa of the esophagus within 3–10 years it was found.